Coplanar waveguide fed ultra‐wideband multiple‐input multiple‐output slot antenna with connected ground and high isolation for internet of things and wireless body area network applications. Issue 12 (14th November 2022) - Du, Chengzhu; Wang, Ruohui; Zhang, Jie
Abstract: This paper proposes two flexible ultra‐wideband (UWB) multiple‐input multiple‐output (MIMO) slot antennas with connected ground and high isolation. Two MIMO antennas consist of two parallel slot antenna elements with coplanar waveguide feeds and ground. The antennas are etched on the liquid crystal polymer substrate and have the consistent sizes of 30 × 56 × 0.1 mm 3 . The first UWB‐MIMO antenna can cover 3–13 GHz. By adding a U‐shaped slot on the first antenna, a second UWB‐MIMO antenna with a notch‐band is designed, which can work in 3.2–13 GHz and filter the wireless fidelity frequency band (5–6 GHz). High isolation better than 20 dB is obtained by adding fence‐shaped branches. In addition, the performance of the flexible MIMO antenna is analyzed, including diversity performance parameters such as envelope correlation coefficient, diversity gain, gain, and total active reflection coefficient. The proposed UWB‐MIMO antenna can be applied in internet of things and wireless body area network frequency bands.